TWO NEW CHRYSOBALANACEAE OF EASTERN NEW GUINEA - kostermans, a. j. g. h. (Research Center for Biology, 1984)
Hunga fusivarpa Kosterm. and Pavinari prancei Kosterm., from Milne Bay Distr., Papua-New Guinea are decribed as new species.